THE ROLE OF THE AUDIT TIME BUDGET IN THE RELATIONSHIP OF AUDITOR COMPETENCY, INDEPENDENCE, AND EXPERIENCE ON AUDIT QUALITY - Isniawati, Atik; Yuliastari, Amanda Reza; Modjaningrat, Radina; Baisyir, Fauzi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to analyze the effect of auditor competence, independence and experience on audit quality with audit time budget as a moderating variable. This study uses primary data with data collection methods using questionnaires with purposive sampling method on 70 auditors at the Public Accounting Firm (KAP) DKI Jakarta area. The findings of this study indicate that auditor competence has a significant positive effect on audit quality. Furthermore, auditor independence has a significant positive effect on audit quality and auditor experience has a significant positive effect on audit quality. The results of the next test prove that the audit time budget moderates the effect of auditor competence on audit quality. However, the audit time budget does not moderate the independence and experience of auditors on audit quality.Keywords: Audit Quality, Audit Time BudgetÂ